Simulation of microstructure development during the hydration of cement-based materials - Ji, Yajun (2008)
T his model explains the effect of the raw materials properties, mix proportion and curing condition on cement hydration, pozzolanic reaction, microstructure and physical properties. If the raw materials properties, mix proportion and curing conditions are known, the microstructure and physical properties of cement-based materials can be predicted.